Location Dominance in Islamic Retail Customer Loyalty: Dominasi Lokasi dalam Loyalitas Pelanggan Ritel Islami - Muhammad Azzam Syarif; Ana Fitriyatul Bilgies; Nurul Fauziyah (Academia Open, 2026)
General Background: Customer loyalty is a central concern in modern retail because repeat purchasing, positive recommendations, and resistance to competitors support sustainable retail performance. Specific Background: This study examined customer loyalty in an Islamic modern retail setting by focusing on price, product quality, and location as key factors in daily-needs purchasing behavior. Knowledge Gap: Prior studies have discussed customer loyalty in various retail contexts, yet limited empirical attention has been given to the simultaneous testing of price, product quality, and location in Islamic value-based modern retail. Aims: This study aimed to analyze how price, product quality, and location relate to customer loyalty among 152 repeat customers. Results: The findings show that all questionnaire items were valid and all variables were reliable. Respondents rated price, product quality, location, and customer loyalty in the high category. Multiple linear regression with robust HC3 standard errors indicated that price, product quality, and location were positive and significant factors in customer loyalty, with location showing the largest coefficient. The model explained 85.7% of customer loyalty variance. Novelty: The study identifies location as the dominant factor within a combined model of price, product quality, and location in Islamic modern retail. Implications: Retail managers should maintain fair pricing, consistent product quality, and accessible store locations, including convenient parking, to support sustainable customer loyalty. Highlights• Price, product quality, and location were all significant factors in customer loyalty.• Location showed the strongest coefficient among the tested variables.• The regression model explained 85.7% of customer loyalty variance. KeywordsCustomer Loyalty; Islamic Retail; Product Quality; Price Perception; Store Location